BEGINNINGS OF PSYCHIATRY IN BAJA CALIFORNIA: MENTAL HEALTH AND DRUG DEPENDENCE, 1964-1989 (Tzintzun, Revista de Estudios Históricos, 2024)
This article looks at the transition of a practical problem into one of knowledge,seeking to situate the first experiences of forerunners of psychiatry in the borderarea between Mexico and the United States, precisely at the time of an openstruggle against drug dependence. Through career histories in hospitals, jails,and drug detoxification clinics, a context will be defined in which sevenpsychiatrists gained knowledge relative to the mentally ill in a region, which hadpsychiatric educational programs and institutions only by the end of the 20thcentury.
Keywords: Psychiatry; Mental illnesses; Drugs; Hospitals; Baja California